“…in the middle of nowhere…” Access to, and quality of, services for autistic adults from parents’ perspectives: a qualitative study - Németh, Vivien; Győri, Miklós; Ehmann, Bea; Völgyesi-Molnár, Márta; Stefanik, Krisztina (Frontiers in Psychiatry, 2024)
Introduction: Adequate education, employment, and services for autistic individuals contribute significantly to their and their parents’ quality of life. Services and support for adults are dramatically more limited than those for children. The main purpose of this study was to explore how parents perceive factors supporting/hindering access to services, and how they assess the quality of services. Methods: Qualitative data provided by 12 parents via a semi-structured interview with a broader focus on parental quality of life and its factors were analyzed. Their autistic children were between 20 and 34 years of age. A thematic analysis was performed on parts of the narratives on their adult periods of life. Results: A complex pattern of parental perception of supportive and hampering factors influencing access to services unfolded. The sparsity of services/activities and reliable information on them made the space for autonomous decisions on service take highly limited. Parents have modest expectations on quality of services, evaluating them along two key aspects: a safe, positive atmosphere, and communication between parents and professionals. Other aspects of individualized autism-specific support were not or just rarely mentioned. Discussion: Parents perceive themselves as investing a lot of effort and resources in getting some form of regular service and/or activity for their adult child. However, these parental efforts often fail, their child becoming inactive, and dependent on their presence. This suggests system-level problems with services for autistic adults in Hungary, with literature showing it is not specific to this country.